Association Between Previous Stroke and Severe COVID-19: A Retrospective Cohort Study and an Overall Review of Meta-Analysis - Huang, Huayao; Chen, Junnian; Fang, Shuangfang; Chen, Xiaoling; Pan, Xiaobin; Lei, Hanhan; Zhang, Yixian; Lin, Hailong; Yuan, Qilin; Xia, Pincang; Liu, Nan; Du, Houwei (Frontiers in Neurology, 2022)
Objectives: To investigate the association between previous stroke and the risk of severe coronavirus disease 2019 (COVID-19). Methods: We included 164 (61.8 ±13.6 years) patients with COVID-19 in a retrospective study. We evaluated the unadjusted and adjusted associations between previous stroke and severe COVID-19, using a Cox regression model. We conducted an overall review of systematic review and meta-analysis to investigate the relationship of previous stroke with the unfavorable COVID-19 outcomes. Results: The rate of severe COVID-19 in patients with previous stroke was 28.37 per 1000-patient days (95% confidence [interval interval, CI] 10.65-75.59), compared to 3.94 per 1000-patient days (95%CI 2.66-5.82) in those without previous stroke (p<0.001). Previous stroke was significantly associated with severe COVID-19 using a Cox regression model (unadjusted [hazard ratio, HR]: 6.98, 95%CI 2.42-20.16, p<0.001; adjusted HR [per additional ten years] 4.62, 95%CI 1.52-14.04, p = 0.007). An overall review of systematic review and meta-analysis showed that previous stroke was significantly associated with severe COVID-19, mortality, need for intensive care unit admission, use of mechanical ventilation, and an unfavorable composite outcome. Conclusions: Previous stroke seems to influence the course of COVID-19 infection; such patients are at high risk of severe COVID-19 and might benefit from early hospital treatment measures and preventive strategy.